Public international law: a practical approach, 4th ed. - Hamid, Abdul Ghafur@Khin Maung Sein (Thomson Reuters Asia Sdn Bhd, 2019)
International law is a fascinating subject which has gone far beyond its traditional idea of the law governing the relations of sovereign States. In the present time, its pervasiveness covers the activities of international organizations, civil society, NGOs and even ordinary citizens of each and every country of the world. International law is everywhere and it touches upon everybody’s business in an increasingly globalized world.